Nitric oxide synthases activation and inhibition by metallacarborane-cluster-based isoform-specific affectors - Kaplánek, Robert; Martásek, Pavel; Grüner, Bohumír; Panda, Satya; Rak, Jakub; Masters, Bettie Sue Siler; Král, Vladimír; Roman, Linda J (Journal of medicinal chemistry, 2012)
A small library of boron-cluster- and metallacarborane-cluster-based ligands was designed, prepared, and tested for isoform-selective activation or inhibition of the three nitric oxide synthase isoforms. On the basis of the concept of creating a hydrophobic analogue of a natural substrate, a stable and nontoxic basic boron cluster system, previously used for boron neutron capture therapy, was modified by the addition of positively charged moieties to its periphery, providing hydrophobic and nonclassical hydrogen bonding interactions with the protein. Several of these compounds show efficacy for inhibition of NO synthesis with differential effects on the various nitric oxide synthase isoforms.
Keywords: chemické modely; Boron Compounds; sloučeniny boru; organokovové sloučeniny; Molecular Structure; protein - isoformy; Protein Isoforms; kobalt; synthasa oxidu dusnatého; Humans; Models, Chemical; lidé; Cobalt; Organometallic Compounds; Nitric Oxide Synthase; molekulární struktura